Analysis of tweets discussing the risk of Mpox among children and young people in school (May-October 2022): a retrospective observational study - Vinay Prasad; Tracy Beth Høeg; Ben Knudsen (BMJ Publishing Group, 2024)
Objective To determine the number of tweets discussing the risk of Mpox to children and young people in school and (1) determine accuracy, (2) for inaccurate tweets, determine if risk was minimised or exaggerated and (3) describe the characteristics of the accounts and tweets which contained accurate versus inaccurate information.Design Retrospective observational study.Setting Twitter advanced search in January 2023 of tweets spanning 18 May 2022-19 September 2022.Participants Accounts labelled as: MD, DO, nurse, pharmacist, physical therapist, other healthcare provider, PhD, MPH, Ed. degree, JD, health/medicine/public policy reporter (including students or candidates) who tweeted about the risk of Mpox to children and young people in school.Exposures Tweets containing the keywords 'school' and 'mpox', 'pox', or 'monkeypox' from May to October 2022.Measures (1) The total and ratio of accurate versus inaccurate tweets, the latter further subdivided by exaggerating or minimising risk, and stratified by account author credential type. (2) The total likes, retweets and follower counts by accurate versus inaccurate tweets, by month and account credentials. (3) Twitter user exposure to inaccurate versus accurate tweets was estimated.Results 262 tweets were identified. 215/262 (82%) were inaccurate and 215/215 (100%) of these exaggerated risks. 47/262 (18%) tweets were accurate. There were 163 (87%) unique authors of inaccurate tweets and 25 (13%) of accurate tweets. Among healthcare professionals, 86% (95/111) of tweets were inaccurate. Multiplying accuracy by followers and retweets, Twitter users were approximately 974× more likely to encounter inaccurate than accurate information.Conclusion Credentialed Twitter users were 4.6 times more likely to tweet inaccurate than accurate messages. We also demonstrated how incorrect tweets can be quickly amplified by retweets and popular accounts. In the case of Mpox in children and young people, incorrect information always exaggerated risks.